PENGEMBANGAN MATERI GO GREEN BAGI SISWA SMA DENGAN PENDEKATAN ACTIVE LEARNING (Pilot Project pada SMA IT Nur Hidayah Sukoharjo) - Purnomowati, Nasyiah Hasanah; Asrihapsari, Andi (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2021)
Global warming and climate change issues and the impacts become worse recently. This condition needs real actions to maintain sustainable living being. One thing that we can do is developing go green lifestyle  for teenagers . It is important because they are  agent of future change. This project aims to build go green mindset for Senior High School students and encourage them to implement their ideas  become real actions. A series of activities were designed by using active learning approach so the students have active roles in each activity. Firstly, we organise a go green poster competition. Secondly, we installed two  hidroponic sets to make the school greener. The winner of the poster competition became green school ambassadors who have responsibilty to maintain  hydroponic installation. They also have to do green campaign around their communities.